2020
DOI: 10.1515/mgmc-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure in lead and zinc mines induces oxidative stress in miners lymphocytes: Role of mitochondrial/lysosomal damage

Abstract: The purpose of this research was to determine mitochondrial and lysosomal damage and oxidative stress status in blood lymphocytes of lead-zinc miners. This research was performed in 10 mine workers who have been in contact with lead and zinc in comparison to a control group containing 10 healthy volunteers. Lymphocytes were isolated from peripheral blood using the Ficoll standard method and then mitochondrial and lysosomal damage and oxidative stress were evaluated. The level of reactive oxygen species (ROS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…An in vitro study made in RAW 264.7 murine macrophages after exposure to 50-150 ppm Cr III exhibited no mT dysfunction. A recent report from Seydi et al [94] showed that Cr VI caused Mt Membrane Potential (MMP) collapse in isolated human lymphocytes. In brief, a surge in the generation of ROS, inhibition of mT respiratory chain complex I and activation of caspase 9 mediate its effects on cell death.…”
Section: Chromium (Cr)mentioning
confidence: 99%
“…An in vitro study made in RAW 264.7 murine macrophages after exposure to 50-150 ppm Cr III exhibited no mT dysfunction. A recent report from Seydi et al [94] showed that Cr VI caused Mt Membrane Potential (MMP) collapse in isolated human lymphocytes. In brief, a surge in the generation of ROS, inhibition of mT respiratory chain complex I and activation of caspase 9 mediate its effects on cell death.…”
Section: Chromium (Cr)mentioning
confidence: 99%
“…While this zinc insufficiency is concerning, however, the overuse of oral zinc supplementation is also an issue, and deaths have been reported due to consuming it in excess [4][5][6]. Additionally, zinc exposure can also stem from industrial or occupational hazards, such as the airborne zinc particulates prominent in mining operations [7,8] or the accidental contamination of food or water from storage in galvanized containers or pipes [4]. These paths of exposure could affect populations nearby, whether through chronic or acute effects, and have health repercussions that are, as of now, not fully understood.…”
Section: Introductionmentioning
confidence: 99%